Evaluation of Total Phenolic and Flavonoid Contents, Antibacterial and Antibiofilm Activities of Hungarian Propolis Ethanolic Extract against Staphylococcus aureus - Sarra Bouchelaghem; Sourav Das; Romen Singh Naorem; Lilla Czuni; Gábor Papp; Marianna Kocsis (Molecules, 2022)
Propolis is a natural bee product that is widely used in folk medicine. This study aimed to evaluate the antimicrobial and antibiofilm activities of ethanolic extract of propolis (EEP) on methicillin-resistant and sensitive Staphylococcus aureus (MRSA and MSSA). Propolis samples were collected from six regions in Hungary. The minimum inhibitory concentrations (MIC) values and the interaction of EEP-antibiotics were evaluated by the broth microdilution and the chequerboard broth microdilution methods, respectively. The effect of EEP on biofilm formation and eradication was estimated by crystal violet assay. Resazurin/propidium iodide dyes were applied for simultaneous quantification of cellular metabolic activities and dead cells in mature biofilms. The EEP1 sample showed the highest phenolic and flavonoid contents. The EEP1 successfully prevented the growth of planktonic cells of S. aureus (MIC value = 50 µg/mL). Synergistic interactions were shown after the co-exposition to EEP1 and vancomycin at 108 CFU/mL. The EEP1 effectively inhibited the biofilm formation and caused significant degradation of mature biofilms (50–200 µg/mL), as a consequence of the considerable decrement of metabolic activity. The EEP acts effectively as an antimicrobial and antibiofilm agent on S. aureus. Moreover, the simultaneous application of EEP and vancomycin could enhance their effect against MRSA infection.